Near-infrared light mediated heterogeneous composite photocatalyst as well as preparation method and application thereof
By designing a near-infrared light-mediated heterogeneous composite photocatalyst, using 980nm near-infrared light to achieve efficient synthesis of dihydroisoquinolinone compounds, the problems of excessive dependence on visible light and catalyst non-recovery in the prior art are solved, and efficient and reusable photocatalytic effect is achieved.
Patent Information
- Application Number
- CN202411818907.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, the synthesis of dihydroisoquinolinone compounds depends on visible light catalysis, and there are problems such as excessive dependence on visible light, unrecoverable catalysts, and difficulty in large-scale industrial production, and the utilization efficiency of near-infrared light is low.
A near-infrared light-mediated heterogeneous composite photocatalyst was designed to support semiconductor materials by upconversion of luminescent materials to achieve photocatalysis under 980nm near-infrared light, specifically including the heterojunction structure of rare earth ion-doped fluoride nanoparticles and Co3O4/g-C3N4 nanosheets.
It has achieved efficient α-oxidized N-substituted tetrahydroisoquinoline compounds under 980nm near-infrared light, broadening the synthesis method of dihydroisoquinoline compounds. The catalyst can be reused and maintained high activity, and is suitable for large-scale industrial production.
Smart Images

Figure CN119633858A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalytic material preparation, and specifically relates to a near-infrared light-mediated heterogeneous composite photocatalyst and a preparation method thereof, and application in synthesizing dihydroisoquinolinone compounds with potential biological activity value. Background Art
[0002] Oxidation is one of the most common and critical transformations in organic chemistry, which is widely used in drug synthesis, natural product modification and material science. In the context of green and sustainable development, visible light-driven photocatalytic organic oxidation systems are becoming an ideal alternative to traditional organic synthesis, and semiconductor photocatalysts have made significant progress in this field. As a new type of semiconductor photocatalyst, graphitic carbon nitride (g-C3N4) has been widely used in visible light-responsive photocatalytic organic transformations and other applications due to its low cost, non-toxicity, recyclability, easy synthesis and excellent structural stability. However, the band gap of g-C3N4 is about 2.7 eV, which limits its ability to effectively utilize light outside the visible spectrum, especially near-infrared light. Although near-infrared light accounts for about 52% of solar energy, this limitation greatly weakens its potential in photocatalytic applications. Therefore, extending the light absorption range of g-C3N4 to the near-infrared region and using near-infrared light to drive organic oxidation reactions can not only achieve more efficient solar energy conversion, but also have important significance for promoting the development of sustainable chemistry and environmental technologies.
[0003] Among various anti-Stokes shift materials, lanthanide-doped upconversion nanoparticles are one of the most effective materials for converting near-infrared light into ultraviolet or visible light. Upconversion luminescent materials uniquely absorb two or more low-energy photons and emit higher-energy photons at shorter wavelengths, thereby achieving conversion from near-infrared light to visible light. Since upconversion luminescent materials undergo fluorescence resonance energy transfer through radiative or non-radiative energy transfer mechanisms, the surrounding semiconductors are able to reabsorb this energy and generate photogenerated carriers, thereby promoting the generation of photocatalytically active species. When upconversion luminescent materials are combined with g-C3N4, the light absorption boundary of g-C3N4 is extended from the visible light range to the near-infrared region. This extension enables g-C3N4 to more effectively absorb and utilize longer wavelength light sources, reduce dependence on ultraviolet and visible light, and thus maximize the utilization efficiency of solar energy, which is of urgent importance for the realization of near-infrared photocatalytic applications.
[0004] Dihydroisoquinolinone, as a useful synthetic precursor of aromatic ketone with biological activity, has been widely used in the development and research of various drug molecules. In addition to being a synthetic precursor, dihydroisoquinolinone also exhibits a variety of important biological activities. For example, its antimalarial effect has been used to develop new antimalarial drugs, showing strong inhibition of malarial parasites; its antitussive effect makes it a potential candidate molecule for the treatment of respiratory diseases, which can effectively relieve cough symptoms. The anti-Parkinson's disease properties of dihydroisoquinolinone also show important potential in the treatment of neurodegenerative diseases, and it is expected to be developed as a new therapeutic drug. Lenalidomide, whose chemical name is 3-(4-amino-1-oxoisoindol-2-yl)piperidine-2,6-dione, was developed by the American Cell Gene Company as a new generation of immunomodulatory drugs of thalidomide. It was approved by the US FDA for marketing in January 2006 for the treatment of myelodysplastic syndrome (MDS) subtypes and multiple myeloma and is widely used in the treatment of various rare diseases.
[0005]
[0006] In the prior art, dihydroisoquinolinone compounds are obtained by α-oxidation reaction of N-substituted tetrahydroisoquinoline compounds catalyzed by visible light. Although the visible light catalytic system has great potential, it has the disadvantages of over-reliance on visible light, non-recyclable catalysts, and difficulty in large-scale industrial production, which leads to the current method of preparing dihydroisoquinolinone compounds still needs to be improved. Near-infrared light energy accounts for 52% of the energy of the entire solar spectrum. Designing a composite photocatalyst that can respond to near-infrared light and developing a heterogeneous photocatalytic system that can achieve α-oxidation of N-substituted tetrahydroisoquinoline compounds under near-infrared light irradiation is of great significance for the research and exploration of the synthesis of biologically active dihydroisoquinolinone compounds. It also provides another more feasible option for the synthesis of 3-(4-nitro-1-oxo-1,3-dihydro-2H-isoindol-2-yl)piperidine-2,6-dione, a key intermediate of lenalidomide. Lenalidomide is obtained by amination of the key intermediate 3-(4-nitro-1-oxo-1,3-dihydro-2H-isoindol-2-yl)piperidine-2,6-dione (III), and its structure is shown below:
[0007]
[0008] The inventors have provided a near-infrared light-mediated heterogeneous composite photocatalyst, and applied it to achieve α-oxidation of N-substituted tetrahydroisoquinoline compounds under 980nm near-infrared light irradiation. This provides a highly feasible option for the production of dihydroisoquinolinone compounds and key intermediates of the drug lenalidomide. Its near-infrared light source is abundant and easy to obtain, the reaction conditions are mild, and the equipment requirements are low; the advantages of near-infrared light can be used to achieve the amplification of the photocatalytic system; the photocatalyst used can be reused many times and is environmentally friendly. Summary of the invention
[0009] One of the purposes of the present invention is to provide a heterogeneous composite photocatalyst with high catalytic efficiency and high recyclability.
[0010] A second object of the present invention is to provide a near-infrared light-mediated heterogeneous composite photocatalyst, which can respond to near-infrared light.
[0011] The third object of the present invention is to provide a method for preparing the near-infrared light-mediated heterogeneous composite photocatalyst.
[0012] The fourth object of the present invention is to provide a near-infrared light-mediated heterogeneous composite photocatalyst for use in the synthesis of biologically active dihydroisoquinolinone compounds, providing a more feasible option for realizing the α-oxidation synthesis of dihydroisoquinolinone compounds by N-substituted tetrahydroisoquinoline compounds under 980nm near-infrared light.
[0013] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0014] A near-infrared light-mediated heterogeneous composite photocatalyst, wherein the heterogeneous composite photocatalyst is an upconversion luminescent material loaded with a semiconductor material, and can achieve upconversion luminescent catalysis under 980nm near-infrared light irradiation; the upconversion luminescent material is a fluoride nanoparticle doped with a rare earth ion, wherein the fluoride is one or both of yttrium fluoride and sodium yttrium tetrafluoride, and the doped rare earth ions include rare earth luminescent center ions and light-absorbing ions, wherein the luminescent center ions include Er 3+ 、Tm 3+ , Tb 3+ , Pr 3+ One of the light-absorbing ions includes Yb 3+ ; The semiconductor material is Co3O4 quantum dots and g-C3N4 nanosheets tightly forming a heterojunction structure; the mass ratio of the upconversion luminescent material to the semiconductor material is 1:1-4, preferably 1:2-3.
[0015] Furthermore, the chemical composition of the up-conversion luminescent material is NaYF4:Yb 3+ / Er 3+ , where Yb3+ The doping concentration is 10-25%, preferably 18-20%, and the light-absorbing ion Yb 3+ With the luminescent central ion Er 3+ The doping ratio is 1:2-12, preferably 1:8-10.
[0016] Furthermore, the Co3O4 quantum dots in the semiconductor material are prepared using vitamin B12 as a cobalt source, and the doping concentration of the Co3O4 quantum dots in the semiconductor material is 0.1-2 mol%, preferably 0.45-1.0 mol%.
[0017] The method for preparing a near-infrared light-mediated heterogeneous composite photocatalyst comprises the following steps:
[0018] (1) taking a rare earth source, a fluorine source and an alkaline substance in a high boiling point organic solvent for solvothermal reaction to form rare earth ion-doped fluoride nanoparticles;
[0019] The rare earth source is a compound of Y, a luminescent central ion element and a light-absorbing ion element Yb, and the compound is one or a combination of two or more of nitrate, oxide, acetate and chloride;
[0020] (2) taking an aqueous solution of vitamin B12 to impregnate the g-C3N4 nanosheets at room temperature, drying after sufficient impregnation, and further heating and calcining in a muffle furnace to form semiconductor Co3O4 / g-C3N4 nanosheets;
[0021] (3) dissolving the rare earth ion-doped fluoride nanoparticles of step (1) in a first solvent and fully mixing the fluoride nanoparticles with the semiconductor Co3O4 / g-C3N4 nanosheets so that the fluoride nanoparticles are evenly distributed on the surface of the semiconductor Co3O4 / g-C3N4 nanosheets, and further drying at high temperature after room temperature immersion to obtain a near-infrared light-mediated heterogeneous composite photocatalyst; the first solvent comprises one or a combination of two or more of methanol, ethanol, acetone, and n-hexane.
[0022] Furthermore, in step (1), the fluorine source includes one or a combination of two or more of ammonium fluoride, sodium fluoride, and potassium fluoride, and the molar amount of the fluorine source is 4-4.5 times the molar amount of compound Y; the alkaline substance includes one or a combination of two or more of sodium hydroxide, potassium hydroxide, and ammonia water, and the molar ratio of the alkaline substance to the fluorine source is 0.5-1.0:1, preferably 0.7-0.75:1; the high boiling point organic solvent includes one or a combination of two or more of ethylene glycol, oleic acid, and dodecene, and the dispersed concentration of the rare earth source in the high boiling point organic solvent is 0.01-0.1 mol / L; the solvent thermal reaction temperature in step (1) is 80-240°C, preferably 200-240°C, and the solvent thermal reaction time is 12-24h, optimized to be 20-24h.
[0023] Furthermore, in step (2), vitamin B12 and g-C3N4 nanosheets are mixed in a mass ratio of (0.1-1):1, preferably (0.1-0.5):1; the heating and calcining temperature in the muffle furnace is 300-600°C, optimized to 500-550°C, and the calcination time is 1-5h, optimized to 3-5h.
[0024] The present invention also discloses the use of the near-infrared light-mediated heterogeneous composite photocatalyst in catalyzing the oxidation of CH at the benzylic position of an alkyl aromatic compound to aromatic ketone. The compound represented by formula (II) is used as a raw material, dispersed in an organic solvent together with the heterogeneous composite photocatalyst and an oxidant, and oxidized under 980nm near-infrared light at room temperature for 12 to 48h with stirring to generate a product represented by formula (I), the structure of which is shown as follows:
[0025]
[0026] In formula (II) and formula (I), X is N or O element, n=0 or 1, indicating that the heterocyclic ring is a five-membered ring or a six-membered ring; R 1 is H, C1-C4 alkyl, C1-C4 alkoxy or aryl, R 2 is a C1-C4 alkyl group, an aryl group, an ester group, an acetyl group or a benzoyl group;
[0027] When X in the compound structure of formula (II) is N, and R 2 When it is a C1-C4 alkyl or aryl group, a base is also added in the above oxidation reaction, and the molar ratio of the base to the compound of formula (II) is 1.2-1.5:1;
[0028] The aryl group is a phenyl group or a substituted phenyl group, and the substituent on the phenyl ring of the substituted phenyl group is a C1-C4 alkyl group.
[0029] That is, when X in the compound structure of formula (II) is N, and R 2 When X is an ester group, an acetyl group or a benzoyl group, and X is O, the above oxidation reaction does not require the addition of a base.
[0030] Furthermore, in the application method, the oxidant is one or a combination of two or more of oxygen and air, and the oxidant gas is continuously introduced into the reaction system during the oxidation reaction. The organic solvent is selected from one or a combination of two or more of tetrahydrofuran, N,N-dimethylformamide, dimethyl sulfoxide, 1,4-dioxane, 1,2-dichloroethane, and acetonitrile.
[0031] Furthermore, in the application method, the ratio of the mass of the heterogeneous composite photocatalyst to the molar amount of the compound of formula (II) is (10-80) mg:1 mmol, preferably (50-60) mg:1 mmol; the near-infrared light source power is selected to be 20-200 W, optimized to be 50-100 W; the base is at least one of potassium carbonate, sodium carbonate, cesium carbonate, and sodium bicarbonate, the molar ratio of the base to the compound of formula (II) is 1.2-1.5:1, and the oxidation reaction time is 30-60 h.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The present invention is based on the anti-Stokes luminescence mechanism. The prepared upconversion material can continuously absorb two or more low-energy photons and emit high-energy photons with shorter wavelengths, thereby realizing the conversion from near-infrared light to visible light.
[0034] (2) The present invention introduces vitamin B12 into the semiconductor material g-C3N4 nanosheet, mixes it with the g-C3N4 nanosheet, and after thermal polymerization in air, quantum dot-scale cobalt oxide can be generated on the g-C3N4 nanosheet. The formation of the Co3O4 / g-C3N4 nanosheet heterojunction can improve the separation efficiency of the hole-electron pairs of the g-C3N4 nanosheet, thereby enhancing the activity of the catalyst. This heterojunction structure can become an electron transmission channel to achieve rapid electron transfer and prevent electron-hole recombination. At the same time, it can effectively increase the contact area with the reaction substrate and provide more sites for the reaction. The above reasons make the catalyst have extremely strong catalytic oxidation activity.
[0035] (3) The present invention combines upconversion luminescent materials rich in near-infrared light with Co3O4 / g-C3N4 nanosheets to form a composite material that can convert near-infrared light into visible green light, which promotes the charge energy transfer within the Co3O4 / g-C3N4 nanosheets, reduces the migration distance of photogenerated carriers, and significantly improves the light absorption efficiency and photogenerated carrier separation efficiency of the photocatalyst in the near-infrared light region, which is beneficial to increase the generation of photocatalytic reaction species and multiple recycling and reuse without deactivation.
[0036] (4) The present invention completely avoids using precious metals as raw materials and has low cost.
[0037] (5) The present invention realizes efficient α-oxidation of N-substituted tetrahydroisoquinoline compounds to dihydroisoquinolinone compounds under the mediation of 980nm near-infrared light, broadens the synthesis method of dihydroisoquinolinone compounds, has mild reaction conditions and low equipment requirements, and is more suitable for large-scale industrial production by utilizing the advantages of near-infrared light.
[0038] (6) The NaYF4,Yb:Er / Co3O4 / g-C3N4 composite photocatalyst of the present invention remains highly active after repeated recycling and use, showing excellent stability and reusability. The present invention not only demonstrates the significant potential of the photocatalyst in synthesizing bioactive intermediates under near-infrared light induction, but also provides important reference and inspiration for the design and development of future photocatalytic systems.
[0039] (7) In the NaYF4,Yb:Er / Co3O4 / g-C3N4 composite photocatalyst of the present invention, the luminescent central ion is Er 3+ It has good photocatalytic performance, while Tm 3+ , Tb 3+ , Pr 3+ The catalytic effects of etc. as luminescent central ions are not ideal. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The comparison results of XRD spectra and FT-IR spectra of NaYF4,Yb:Er / Co3O4 / g-C3N4 nanosheets prepared by using different mass ratios of "NaYF4,Yb:Er and Co3O4 / g-C3N4" in Examples 1-3 and "the standard case of NaYF4,Yb:Er" are shown; Figure 1 (a) is the XRD spectra of all heterogeneous composite photocatalysts in Examples 1-3 and the "standard case of Na YF4, Yb: Er"; Figure 1 (b) is the FT-IR spectrum of the heterogeneous composite photocatalyst in Example 2 and the "standard case of NaYF4, Yb:Er".
[0041] Figure 2a It is a fluorescence spectrum diagram of the heterogeneous composite photocatalyst of Examples 1-3 of the present invention and the "standard case of NaYF4, Yb: Er" under 980nm near-infrared wavelength excitation;
[0042] Figure 2b is the attenuation curve of the heterogeneous composite photocatalyst of Example 2 and the "standard case of NaYF4, Yb: Er" at a wavelength of 541 nm;
[0043] Figure 2c This is the upconversion spectrum of the "standard case of NaYF4, Yb: Er" in the visible light region.
[0044] Figure 2d It is a double logarithmic coordinate diagram of the integrated intensity of the up-conversion spectral band corresponding to different excitation intensities of the "standard case of NaYF4, Yb: Er".
[0045] Figure 3aThis is the corresponding relationship between the yield of the target product "2-phenyl-3,4-dihydroisoquinolin-1(2H)-one" in Example 2 and the number of times the catalyst is used.
[0046] Figure 3b This is a comparison result of the XRD patterns of the fresh heterogeneous composite photocatalyst prepared in Example 2 and the catalyst after being used 7 times.
[0047] Figure 4 This is the mechanism of action of the heterogeneous composite photocatalyst in specific embodiment 2 under the mediation of 980nm near-infrared light. DETAILED DESCRIPTION
[0048] The present invention is further described below in conjunction with specific embodiments, but these embodiments are only intended to illustrate the present invention rather than further limit the protection scope of the present invention.
[0049] The schematic diagram of the mechanism of action of the heterogeneous composite photocatalyst of the present invention under the mediation of 980nm near-infrared light is as follows Figure 4 As shown in the figure, it can be seen that under the continuous excitation of 980nm near-infrared light, Yb 3+ absorbs a photon and rises from the ground state ( 2 F 7 / 2 ) transitions to the excited state ( 2 F 5 / 2 ). Subsequently, Yb in this excited state 3+ Transferring energy to the adjacent Er 3+ , filled with Er 3+ of 2 H 11 / 2 , 4 S 3 / 2 and 4 F 9 / 2 Energy level. 3+ Upconversion luminescence is produced by radiative transition: 2 H 11 / 2 arrive 4 I 15 / 2 and 4 S 3 / 2 arrive 4 I 15 / 2 The transition from 4 F 9 / 2 arrive 4 I 15 / 2 The transition of Yb produces red fluorescence. 3+ It not only exhibits a large absorption cross section for 980nm light, but also has the same 3+ The ff transitions are well consistent with the energy level transitions. 3+ Absorbed from Yb 3+The energy transferred, transitions to a higher energy state and produces upconversion luminescence. This luminescence is achieved by energy transfer to Co3O4 / g-C3N4 nanosheets. In the presence of light, the heterojunction formed between Co3O4 quantum dots synthesized by thermal polymerization of VB12 and g-C3N4 nanosheets demonstrates the effective separation of photogenerated electrons and holes. The photogenerated electrons migrate to the Co3O4 quantum dots, where they reduce oxygen to generate superoxide anions (O2 - ), while the photogenerated holes in the valence band of g-C3N4 nanosheets exhibit a strong oxidation potential, promoting the generation of O2. This efficient separation and transfer of electrons and holes minimizes the recombination rate and improves the photocatalytic efficiency. Combining the upconversion properties of NaYF4,Yb:Er with the photocatalytic properties of Co3O4 / g-C3N4 nanosheets achieves a wider range of light absorption and higher photocatalytic efficiency.
[0050] Example 1
[0051] A method for preparing a near-infrared light-mediated heterogeneous composite photocatalyst is prepared according to the following steps:
[0052] (1) Preparation of upconversion luminescent materials (NaYF4, Yb:Er): Weigh 0.2 mmol of rare earth nitrate into a 50 mL beaker, where Y 3+ :Yb 3+ :RE 3+ =78:20:2(RE 3+ For up-conversion luminescent ions), add 10mL of oleic acid and keep it under magnetic stirring at 600rpm for 10min. After the rare earth nitrate and oleic acid are evenly mixed, take 0.8mmol sodium fluoride and 0.6mmol sodium hydroxide and dissolve them in 10mL of ethanol and keep it under magnetic stirring at 600rpm for 10min. Then mix the two solutions evenly and put them into a hydrothermal reactor to react at 240℃ for 24h. After the reaction is completed and cooled and allowed to stand, filter and wash the final product with ethanol several times to obtain an up-conversion luminescent material.
[0053] (2) Preparation of Co3O4 / g-C3N4 nanosheets: 200 mg of vitamin B12 and 1 g of g-C3N4 nanosheets were dissolved in 5 mL of deionized water at room temperature for 12 h, and then dried at 100 °C for 12 h. The dried mixture was collected and calcined at 550 °C in air at a heating rate of 5 °C / min for 4 h to obtain Co3O4 / g-C3N4 nanosheets.
[0054] (3) Preparation of heterogeneous composite photocatalyst: The prepared NaYF4, Yb: Er and Co3O4 / g-C3N4 nanosheets were mixed and dispersed in 3 mL of ethanol at a mass ratio of 1:1, and ultrasonicated for 30 min to make NaYF4, Yb: Er evenly distributed on the surface of Co3O4 / g-C3N4 nanosheets. After immersion at room temperature for 12 h, and then dried at 100 ° C for 12 h, the NaYF4, Yb: Er / Co3O4 / g-C3N4 nanosheet composite material was obtained, which was applied to the study of photocatalytic reactions.
[0055] Application of near-infrared photocatalytic oxidation to synthesize dihydroisoquinolinone compounds:
[0056]
[0057] 2-phenyl-1,2,3,4-tetrahydroisoquinoline (0.5mmol), potassium carbonate (0.75mmol, 1.5equiv.) and 30mgNaYF4,Yb:Er / Co3O4 / g-C3N4 nanosheets were dispersed in 5mL dimethyl sulfoxide reaction solvent. Oxygen was continuously introduced into the reaction system, and the reaction was stirred at room temperature and atmospheric pressure for 36h under an oxygen atmosphere and 100W / 980nm near-infrared light irradiation to promote the formation of the target compound. After the reaction, the solid catalyst was removed by filtration, and then the solvent was removed to obtain a crude product. The crude product was separated and purified by column chromatography using petroleum ether / ethyl acetate (10:1, volume ratio) as an eluent, and finally a light yellow oily liquid 2-phenyl-3,4-dihydroisoquinoline-1(2H)-one was obtained with a yield of 27%.
[0058] 1 H NMR(400MHz,Chloroform-d)δ8.20(dd,J=7.7,1.5Hz,1H),7.48(dd,J=7.5,1.5H z,1H),7.41(m,5H),7.31–7.23(m,2H),4.44–3.75(m,2H),3.16(t,J=6.4Hz,2H). 13 CNMR(101MHz,Chloroform-d)δ164.25,143.14,138.37,132.09,129.73,128.95,128.75,127.22,127.02,126.29,125.37,49.45,28.63.
[0059] HRMS(ESI)m / z Calcd for C 15 H 13 NO[M+H] + =224.1070,found:224.1065.
[0060] The filtered and recovered solid catalyst NaYF4, Yb: Er / Co3O4 / g-C3N4 nanosheets were thoroughly washed with ethanol (5×3 mL) and deionized water (5×3 mL), the solid and the washing liquid were separated by centrifugation, and then dried at 60°C for 6 h and used again in the next batch of photocatalytic reactions.
[0061] Example 2
[0062] A method for preparing a near-infrared light-mediated heterogeneous composite photocatalyst is prepared according to the steps of Example 1, the only difference being that in step (3), NaYF4, Yb:Er and Co3O4 / g-C3N4 nanosheets are mixed in a mass ratio of 1:2, and the other conditions remain unchanged, and finally the corresponding heterogeneous composite photocatalyst is prepared.
[0063] The heterogeneous composite photocatalyst of Example 2 was applied to the reaction of synthesizing dihydroisoquinolinone compounds by near-infrared photocatalytic oxidation. The catalytic reaction conditions were carried out according to the steps of Example 1, and finally a light yellow oily liquid 2-phenyl-3,4-dihydroisoquinolin-1(2H)-one was obtained with a yield of 96%.
[0064] The repeated recovery experiment of NaYF4,Yb:Er / Co3O4 / g-C3N4 nanosheets in Example 2 was carried out according to the method of Example 1, and the recovered catalyst was used again in the next batch of photocatalytic reactions. According to this method, the yield of the target product "2-phenyl-3,4-dihydroisoquinolin-1(2H)-one" under different recycling times of the heterogeneous composite photocatalyst in Example 2 and the corresponding relationship between the number of times the catalyst was used are shown in Figure 3a .
[0065] The XRD patterns of the fresh heterogeneous composite photocatalyst prepared in Example 2 and the catalyst after being used for 7 times are shown in FIG. Figure 3b , Figure 3b The inset shows a photo of the catalyst taken under sunlight and 980nm near-infrared light after it was used seven times.
[0066] from Figure 3a-Figure 3b It can be seen that the catalyst maintains high photocatalytic activity when applied to catalytic oxidation, and the crystal structure of the catalyst remains intact even after being reused seven times compared to the fresh catalyst shown. Figure 3b The accompanying image shows the NaYF4,Yb:Er / Co3O4 / g-C3N4 nanosheet catalyst after being reused seven times under sunlight and 980nm near-infrared light. It is clear that under 980nm near-infrared light, the catalyst continues to emit bright green luminescence, further confirming its excellent cycling stability.
[0067] Example 3
[0068] A method for preparing a near-infrared light-mediated heterogeneous composite photocatalyst is prepared according to the steps of Example 1, the only difference being that in step (3), NaYF4, Yb:Er and Co3O4 / g-C3N4 nanosheets are mixed in a mass ratio of 1:3, and the other conditions remain unchanged, and finally the corresponding heterogeneous composite photocatalyst is prepared.
[0069] The heterogeneous composite photocatalyst of Example 3 was applied to the reaction of synthesizing dihydroisoquinolinone compounds by near-infrared photocatalytic oxidation. The catalytic reaction conditions were carried out according to the steps of Example 1, and finally a light yellow oily liquid 2-phenyl-3,4-dihydroisoquinolin-1(2H)-one was obtained with a yield of 88%.
[0070] The repeated recovery experiment of NaYF4, Yb: Er / Co3O4 / g-C3N4 nanosheets was carried out according to the method of Example 1.
[0071] Examples 1-3 use different mass ratios of "NaYF4, Yb: Er to Co3O4 / g-C3N4" to prepare NaYF4, Yb: Er / Co3O4 / g-C3N4 nanosheets, which are marked as "1:1", "1:2", and "1:3" nanosheets, respectively. The NaYF4, Yb: Er prepared in step (1) of Example 1 is marked as "standard case of NaYF4, Yb: Er".
[0072] The XRD characterization results of the above-mentioned “1:1”, “1:2”, “1:3” nanosheets and “NaYF4, Yb: Er standard case” are shown in Figure 1 (a) FT-IR spectra of “1:2” nanosheets and “standard case of NaYF4, Yb: Er” are shown in Figure 1 (b).
[0073] Figure 1 (a) shows that the NaYF4,Yb:Er / Co3O4 / g-C3N4 nanosheets (1:1-3) sample exhibits a diffraction pattern similar to that of NaYF4,Yb:Er, which is successfully matched with the standard PDF card (JCPDS#28-1192) of hexagonal NaYF4. In addition, the relatively weak peak at 27.82° corresponds to the (002) crystal plane of the typical graphite layer in carbon nitride (g-C3N4). However, for the sample with the addition of Co3O4 / g-C3N4 nanosheets, almost no peaks related to cobalt species are observed, which is most likely due to the low cobalt content in the composite material.
[0074] Figure 1(b) shows the Fourier transform infrared (FT-IR) spectrum of NaYF4,Yb:Er / Co3O4 / g-C3N4 nanosheets (mass ratio 1:2). NaYF4,Yb:Er at 3440cm -1 There is a broad absorption peak at 1632-1246cm, which corresponds to the OH stretching vibration. -1 The peaks at and are attributed to HOH bending vibration and CH bending vibration, respectively. 3+ ) may be masked by the vibration peak of the NaYF4 matrix. -1 The absorption peak at is related to the YF stretching vibration in the NaYF4 matrix. The characteristic peaks of carbon nitride (g-C3N4) nanosheets are retained in the infrared spectrum of the composite material, mainly due to its stable and unique vibration mode and complementarity with other components. These factors ensure that the vibration peaks of carbon nitride (g-C3N4) are still clearly visible in the composite material. This shows that the incorporation of Co3O4 / g-C3N4 nanosheets into NaYF4,Yb:Er does not change the original structure of upconversion nanoparticles (UCNPs), which is consistent with the XRD results.
[0075] Broadening the spectral range by using infrared upconversion nanoparticles (UCNPs) to enable the utilization of photocatalysts in the solar spectrum requires that the emission spectrum of the UCNPs matches the response spectrum of the photocatalyst. Figure 2a The fluorescence spectra of "1:1", "1:2", "1:3" nanosheets and NaYF4, Yb: Er are shown under 980 nm near-infrared (NIR) excitation, showing characteristic emission in the visible and near-infrared regions. The emission peaks are located at 524, 541 and 657 nm, which correspond to Er, 3+ Radiative transition: 2 H 11 / 2→ 4 I 15 / 2, 4 S3 / 2→ 4 I 15 / 2 and 4 F9 / 2→ 4 I 15 / 2. Compared with the fluorescence emission intensity at 524 and 541nm, the emission at 657nm is negligible, which makes NaYF4,Yb:Er produce bright green upconversion fluorescence emission. With the increase of the loading amount of Co3O4 / g-C3N4 nanosheets, the emission peak intensity of NaYF4,Yb:Er at 524 and 541nm decreases significantly. This phenomenon indicates that the upconversion emission fluorescence in the visible light region, especially in the green light range (520–560nm), is completely absorbed by Co3O4 / g-C3N4 nanosheets, which is most likely due to the Forster resonance energy transfer (FRET) effect between NaYF4,Yb:Er and Co3O4 / g-C3N4 nanosheets. This phenomenon provides strong evidence for light energy transfer.
[0076] In order to further confirm the Förster resonance energy transfer effect between NaYF4,Yb:Er and Co3O4 / g-C3N4 nanosheets, the fluorescence lifetime decay curves of the samples were tested. 3+ At 541nm( 4 S3 / 2→ 4 I 15 / 2) showed that their average lifespans were 0.731ms and 0.668ms ( Figure 2b ). These results indicate that the combination of NaYF4, Yb:Er and Co3O4 / g-C3N4 nanosheets significantly shortens the Er 3 + The fluorescence lifetime of NaYF4,Yb:Er was 2.3 times that of Co3O4 / g-C3N4 nanosheets, which proves that the nanocomposite promotes the Förster resonance energy transfer from NaYF4,Yb:Er to Co3O4 / g-C3N4 nanosheets under 980nm near-infrared light excitation. The existence of this effect provides a scientific basis for the enhancement of the catalytic activity of NaYF4,Yb:Er / Co3O4 / g-C3N4 nanosheets. It is worth noting that the synthesized NaYF4,Yb:Er exhibits a relatively long decay lifetime, which indicates that upconversion nanoparticles can more effectively convert low-energy light into high-energy light, thereby improving the photoconversion efficiency.
[0077] The upconversion luminescence process involves multiple photons. By studying the relationship between the upconversion luminescence intensity and the excitation light luminescence intensity, the electron transition process and energy transfer in the upconversion process are revealed. The upconversion spectra of NaYF4 and Yb:Er were selected and tested under different excitation intensities. Figure 2d The double logarithmic plots of the integrated intensity of the upconversion spectral bands at different excitation powers are shown. Figure 2cThe upconversion spectrum of the sample in the visible light region is shown. The relationship between the upconversion luminescence intensity (I) and the excitation power (P) satisfies the following equation:
[0078] I∝P n
[0079] Perform double logarithmic processing on this formula:
[0080] Ln(I)∝nln(P) (1)
[0081] The slope represents the number of photons (n), which is obtained by linear fitting with the logarithm of the excitation power (P) as the horizontal axis and the logarithm of the luminescence emission intensity (I) as the vertical axis. The experimental data were fitted according to formula (1). For NaYF4,Yb:Er under 980 nm near-infrared excitation, the slope corresponding to the bright green emission at 541 nm is 2.23, and the slope corresponding to the red upconversion luminescence at 657 nm is 1.89. These values indicate that the upconversion luminescence of NaYF4,Yb:Er mainly involves a two-photon process.
[0082] Example 4
[0083] The heterogeneous composite photocatalyst of Example 2 was used to carry out a near-infrared photocatalytic oxidation reaction to synthesize dihydroisoquinolinone compounds. The catalytic reaction conditions were carried out according to the steps of Example 1, except that "2-phenyl-1,2,3,4-tetrahydroisoquinoline was replaced with an equal molar amount of 6,7-dimethoxy-2-phenyl-1,2,3,4-tetrahydroisoquinoline", and other conditions remained unchanged, and finally a light yellow oily liquid 6,7-dimethoxy-2-phenyl-3,4-dihydroisoquinolin-1(2H)-one was obtained with a yield of 75%. The specific catalytic reaction of Example 4 is as follows:
[0084]
[0085] 6,7-dimethoxy-2-phenyl-3,4-dihydroisoquinolin-1(2H)-one
[0086] 1 H NMR(600MHz,Chloroform-d)δ7.68(s,1H),7.44–7.38(m,4H),7.25(t,J=7.1Hz,1H ), 6.71 (s, 1H), 4.02 (d, J = 3.8Hz, 2H), 3.95 (d, J = 8.5Hz, 6H), 3.08 (t, J = 6.5Hz, 2H). 13C NMR (151MHz, Chloroform-d) δ164.25,152.23,148.18,143.38,132.18,128.88,126.10,125.35,122.28,11.095,109.31,56.14,49.67,28.32.
[0087] HRMS(ESI)m / z Calcd for C 17 H 18 NO3[M+H] + =284.1281,found:284.1272.
[0088] The repeated recovery experiment of NaYF4, Yb: Er / Co3O4 / g-C3N4 nanosheets was carried out according to the method of Example 1.
[0089] Example 5
[0090] The heterogeneous composite photocatalyst of Example 2 was used to carry out the near-infrared photocatalytic oxidation reaction to synthesize dihydroisoquinolinone compounds:
[0091]
[0092] 1-(3,4-dihydroisoquinolin-2(1H)-yl)ethan-1-one (0.5mmol) and NaYF4,Yb:Er / Co3O4 / g-C3N4 nanosheets (30mg) were dispersed in dimethyl sulfoxide (5mL) reaction solvent. Oxygen was continuously introduced into the reaction system, and the reaction was stirred at room temperature and atmospheric pressure for 15h under an oxygen atmosphere and 100W / 980nm near-infrared light irradiation to promote the formation of the target compound. After the reaction was completed, the solid catalyst was removed by filtration, and then the solvent was removed to obtain a crude product. The crude product was separated and purified by column chromatography using petroleum ether / ethyl acetate (5:1, volume ratio) as an eluent, and finally a light yellow oily liquid 2-acetyl-3,4-dihydroisoquinolin-1(2H)-one was obtained with a yield of 83%.
[0093] 2-acetyl-3,4-dihydroisoquinolin-1(2H)-one
[0094] 1 H NMR(400MHz,Chloroform-d)δ8.15(dd,J=7.9,1.4Hz,1H),7.52(m,1H),7.39(m,1 H),7.26(d,J=7.6Hz,1H),4.16–4.06(m,2H),3.00(t,J=6.2Hz,2H),2.67(s,3H). 13CNMR(101MHz,Chloroform-d)δ173.79,165.79,140.31,133.45,129.55,129.04,127.42,41.76,28.15,27.69.
[0095] HRMS(ESI)m / z Calcd for C 11 H 12 NO2[M+H] + =190.0863,found:190.0860.
[0096] The repeated recovery experiment of NaYF4, Yb: Er / Co3O4 / g-C3N4 nanosheets was carried out according to the method of Example 1.
[0097] Example 6
[0098] The heterogeneous composite photocatalyst of Example 2 was used to carry out a near-infrared photocatalytic oxidation reaction to synthesize dihydroisoquinolinone compounds. The catalytic reaction conditions were carried out according to the steps of Example 5, except that "1-(3,4-dihydroisoquinolin-2(1H)-yl)ethan-1-one was replaced with an equal molar amount of 6,7-dimethoxy-3,4-dihydroisoquinoline-2(1H)-benzyl carboxylate", and other conditions remained unchanged. Finally, a light yellow oily liquid 6,7-dimethoxy-1-oxo-3,4-dihydroisoquinoline-2(1H)-benzyl carboxylate was obtained with a yield of 67%. The specific catalytic reaction formula of Example 5 is as follows:
[0099]
[0100] benzyl 6,7-dimethoxy-1-oxo-3,4-dihydroisoquinoline-2(1H)-carboxylate
[0101] 1 H NMR(400MHz,Chloroform-d)δ7.67(s,1H),7.51(d,J=6.8Hz,2H),7.40(t,J=7.3Hz,2H),7.37–7.33 (m,1H),6.66(s,1H),5.37(s,2H),4.13–4.07(m,2H),3.94(d,J=5.8Hz,6H),2.96(t,J=6.2Hz,2H). 13C NMR(101MHz,Chloroform-d)δ163.72,154.75,153.27,148.37,135.59,134.10,12 8.68,128.35,128.13,121.41,111.38,109.24,68.76,56.21,56.19,45.11,28.05.
[0102] HRMS(ESI)m / z Calcd for C 19 H 20 NO5[M+H] + =342.1336,found:342.1323.
[0103] The repeated recovery experiment of NaYF4, Yb: Er / Co3O4 / g-C3N4 nanosheets was carried out according to the method of Example 1.
[0104] Example 7
[0105] The heterogeneous composite photocatalyst of Example 2 was used to carry out the near-infrared photocatalytic oxidation reaction to synthesize dihydroisoquinolinone compounds. The catalytic reaction conditions were carried out according to the steps of Example 1, except that "2-phenyl-1,2,3,4-tetrahydroisoquinoline was replaced with an equal molar amount of 2-phenylisoindoline, and the reaction was carried out under 100W / 980nm near-infrared light irradiation in an oxygen atmosphere for 20 hours to promote the formation of the target compound", and other conditions remained unchanged, and finally a light yellow oily liquid 2-phenylisoindoline-1-one was obtained with a yield of 70%. The specific catalytic reaction formula of Example 7 is as follows:
[0106]
[0107] 2-phenylisoindolin-1-one
[0108] 1 H NMR(400MHz, DMSO-d6)δ7.94–7.90(m,2H),7.80(d,J=7.6Hz,1H),7.72–7.66( m,2H),7.58–7.54(m,1H),7.49–7.41(m,2H),7.22–7.15(m,1H),5.03(s,2H). 13 C NMR (101MHz, DMSO-d6) δ167.13,141.50,139.95,132.90,132.72,129.44,128.65,124.57,123.80,123.70,119.78,50.87.
[0109] HRMS(ESI)m / z Calcd for C 14 H 12 NO[M+H] + =210.0913,found:210.0920.
[0110] Example 8
[0111] The heterogeneous composite photocatalyst of Example 2 was used to carry out a near-infrared photocatalytic oxidation reaction to synthesize dihydroisoquinolinone compounds. The catalytic reaction conditions were carried out according to the steps of Example 1, except that "2-phenyl-1,2,3,4-tetrahydroisoquinoline was replaced with an equal molar amount of 2-(p-tolyl)isoindoline, and the reaction was carried out under 100W / 980nm near-infrared light irradiation in an oxygen atmosphere for 20 hours to promote the formation of the target compound", and other conditions remained unchanged, and finally a light yellow oily liquid 2-(p-tolyl)isoindoline-1-one was obtained with a yield of 68%.
[0112] The specific catalytic reaction formula of Example 8 is as follows:
[0113]
[0114] 2-(p-tolyl)isoindolin-1-one
[0115] 1 H NMR (400MHz, DMSO-d6) δ7.78(dd,J=8.2,3.3Hz,3H),7.66(dd,J=6.3,1.3Hz,2H),7.54(m,1H),7.24(d,J=8.3Hz,2H),4.97(s,2H),2.30(s,3H). 13 C NMR (101MHz, DMSO-d6) δ166.91,141.42,137.48,133.67,133.00,132.55,129.80,128.60,123.73,123.59,119.79,50.91,20.89.
[0116] HRMS(ESI)m / z Calcd for C 15 H 14 NO[M+H] + =224.1070,found:224.1076.
[0117] Example 9
[0118] The heterogeneous composite photocatalyst of Example 2 was used to carry out the near-infrared photocatalytic oxidation reaction to synthesize dihydroisoquinolinone compounds:
[0119] 3-(4-nitro-1,3-dihydro-2H-isoindol-2-yl)piperidine-2,6-dione (0.5mmol), potassium carbonate (0.75mmol, 1.5equiv.) and 30mg NaYF4,Yb:Er / Co3O4 / g-C3N4 nanosheets were dispersed in 5mL 1,4-dioxane reaction solvent. Oxygen was continuously introduced into the reaction system, and the reaction was stirred at room temperature and atmospheric pressure for 24h under oxygen atmosphere and 100W / 980nm near-infrared light irradiation to promote the formation of the target compound. After the reaction, the solid catalyst was removed by filtration, and then the solvent was removed to obtain a crude product. The crude product was separated and purified by column chromatography using petroleum ether / ethyl acetate (3:1, volume ratio) as an eluent, and slurrying was performed to obtain an off-white solid 3-(4-nitro-1-oxo-1,3-dihydro-2H-isoindol-2-yl)piperidine-2,6-dione with a yield of 30.98% and an HPLC purity of 95.5%. The reaction formula of the catalytic reaction of Example 9 is as follows:
[0120]
[0121] 1 H NMR (400MHz, DMSO-d6) δ11.03(s,1H),8.47(d,J=7.7Hz,1H),8.19(d,J=7.3Hz,1H),7.84(t,J=7.8Hz,1 H),5.18(dd,J=13.1,5.1Hz,1H),4.95-4.76(m,2H),2.92(m,1H),2.64-2.51(m,2H),2.10-1.98(m,1H).
[0122] The repeated recovery experiment of NaYF4, Yb: Er / Co3O4 / g-C3N4 nanosheets was carried out according to the method of Example 1.
Claims
1. A near-infrared light-mediated heterogeneous composite photocatalyst, characterized in that: The heterogeneous composite photocatalyst is an upconversion luminescent material loaded with a semiconductor material, which can achieve upconversion luminescent catalysis under 980nm near-infrared light irradiation; The up-conversion luminescent material is a fluoride nanoparticle doped with rare earth ions, wherein the fluoride is one or both of yttrium fluoride and sodium yttrium tetrafluoride, and the doped rare earth ions include rare earth luminescent center ions and light-absorbing ions, wherein the luminescent center ions include Er 3+ 、Tm 3+ , Tb 3+ , Pr 3+ One of the light-absorbing ions includes Yb 3+ ; The semiconductor material is Co3O4 quantum dots and g-C3N4 nanosheets tightly forming a heterojunction structure; The mass ratio of the up-conversion luminescent material to the semiconductor material is 1:1-4, preferably 1:2-3.
2. A near-infrared light-mediated heterogeneous composite photocatalyst as claimed in claim 1, characterized in that: The chemical composition of the up-conversion luminescent material is NaYF4:Yb 3+ / Er 3+ , where Yb 3+ The doping concentration is 10-25%, preferably 18-20%, and the light-absorbing ion Yb 3+ With the luminescent central ion Er 3+ The doping ratio is 1:2-12, preferably 1:8-10.
3. A near-infrared light-mediated heterogeneous composite photocatalyst as claimed in claim 1, characterized in that: The Co3O4 quantum dots in the semiconductor material are prepared by using vitamin B12 as a cobalt source. The doping concentration of the Co3O4 quantum dots in the semiconductor material is 0.1-2 mol%, preferably 0.45-1.0 mol%.
4. The method for preparing a near-infrared light-mediated heterogeneous composite photocatalyst according to claim 1, characterized in that: The following steps are involved: (1) taking a rare earth source, a fluorine source and an alkaline substance in a high boiling point organic solvent for solvothermal reaction to form rare earth ion-doped fluoride nanoparticles; The rare earth source is a compound of Y, a luminescent central ion element and a light-absorbing ion element Yb, and the compound is one or a combination of two or more of nitrate, oxide, acetate and chloride; (2) taking an aqueous solution of vitamin B12 to impregnate the g-C3N4 nanosheets at room temperature, drying after sufficient impregnation, and further heating and calcining in a muffle furnace to form semiconductor Co3O4 / g-C3N4 nanosheets; (3) dissolving the rare earth ion-doped fluoride nanoparticles of step (1) in a first solvent and fully mixing the fluoride nanoparticles with the semiconductor Co3O4 / g-C3N4 nanosheets so that the fluoride nanoparticles are evenly distributed on the surface of the semiconductor Co3O4 / g-C3N4 nanosheets, and further drying at high temperature after room temperature immersion to obtain a near-infrared light-mediated heterogeneous composite photocatalyst; the first solvent comprises one or a combination of two or more of methanol, ethanol, acetone, and n-hexane.
5. The method for preparing a near-infrared light-mediated heterogeneous composite photocatalyst according to claim 4, characterized in that: In step (1), the fluorine source includes one or a combination of two or more of ammonium fluoride, sodium fluoride, and potassium fluoride, and the molar amount of the fluorine source is 4-4.5 times the molar amount of the Y compound; the alkaline substance includes one or a combination of two or more of sodium hydroxide, potassium hydroxide, and ammonia water, and the molar ratio of the alkaline substance to the fluorine source is 0.5-1.0:1, preferably 0.7-0.75:1; the high boiling point organic solvent includes one or a combination of two or more of ethylene glycol, oleic acid, and dodecene, and the dispersion concentration of the rare earth source in the high boiling point organic solvent is 0.01-0.1 mol / L; the solvent thermal reaction temperature of step (1) is 80-240°C, preferably 200-240°C, and the solvent thermal reaction time is 12-24h, optimized to be 20-24h.
6. The method for preparing a near-infrared light-mediated heterogeneous composite photocatalyst according to claim 4, characterized in that: In step (2), vitamin B12 and g-C3N4 nanosheets are mixed in a mass ratio of (0.1-1):1, preferably (0.1-0.5):1; the heating and calcining temperature in the muffle furnace is 300-600°C, optimized to 500-550°C, and the calcination time is 1-5h, optimized to 3-5h.
7. Use of a near-infrared light-mediated heterogeneous composite photocatalyst as claimed in claim 1 in catalyzing the oxidation of CH at the benzylic position of an alkyl aromatic compound to an aromatic ketone, characterized in that: The compound represented by formula (II) is used as a raw material, dispersed in an organic solvent together with a heterogeneous composite photocatalyst and an oxidant, and oxidized under 980nm near-infrared light at room temperature for 12 to 48 hours with stirring to generate a product represented by formula (I), the structure of which is shown below: In formula (II) and formula (I), X is N or O element, n=0 or 1, indicating that the heterocyclic ring is a five-membered ring or a six-membered ring; R 1 is H, C1-C4 alkyl, C1-C4 alkoxy or aryl, R 2 is a C1-C4 alkyl group, an aryl group, an ester group, an acetyl group or a benzoyl group; When X in the compound structure of formula (II) is N, and R 2 When it is a C1-C4 alkyl or aryl group, a base is also added in the above oxidation reaction, and the molar ratio of the base to the compound of formula (II) is 1.2-1.5:1; The aryl group is a phenyl group or a substituted phenyl group, and the substituent on the phenyl ring of the substituted phenyl group is a C1-C4 alkyl group.
8. The use according to claim 7, characterized in that: The oxidant is one or a combination of two or more of oxygen and air. During the oxidation reaction, the oxidant gas is continuously introduced into the reaction system. The organic solvent is selected from one or a combination of two or more of tetrahydrofuran, N,N-dimethylformamide, dimethyl sulfoxide, 1,4-dioxane, 1,2-dichloroethane, and acetonitrile.
9. The use according to claim 7, characterized in that: The ratio of the mass of the heterogeneous composite photocatalyst to the molar amount of the compound of formula (II) is (10-80) mg:1 mmol, preferably (50-60) mg:1 mmol; the power of the near-infrared light source is selected to be 20-200 W, optimized to be 50-100 W; the base is at least one of potassium carbonate, sodium carbonate, cesium carbonate, and sodium bicarbonate, and the oxidation reaction time is 30-60 h.
Citation Information
Cited By
Photo-thermal-electric coupling titanium-based implant as well as preparation method and application thereof
CN121041516A